Identifikasi Pengaruh Ketinggian Tempat terhadap Morfologi Talas Beneng (Xanthosoma undipes K Koch) - Adelia Isti Agustin; Nuniek Hermita; Andi Apriany Fatmawaty; AM Kartina (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
The genetic diversity of beneng taro can be known by analyzing morphological characters. This study aimed to determine the differences in morphological characters in beneng taro plants influenced by altitude using PCA and identify the level of uniformity of morphological characters in beneng taro plants using cluster analysis. This research is a qualitative study with a descriptive approach that is an exploratory survey. Sampling was carried out using a purposive sampling technique. In this study, samples were taken from three different altitudes, namely 343 masl (low), 615 masl (medium), and 761 masl (high) located in Serang Regency and Pandeglang Regency. Ten samples were taken in each location, so 30 taro beneng plants were collected. The research was conducted from January 2024 to March 2024. The variables observed in this study were morphological characters consisting of leaf blade color, leaf bone color, petiole color, plant height, leaf length, leaf width, and petiole length. The results showed that based on PCA, the characters that differed due to altitude were plant height, leaf blade color, leaf bone color, petiole color, petiole length, leaf length, and leaf width. In cluster analysis, 4 clusters were formed, indicating that the uniformity of the characters is relatively broad. Suggestions for further research on root and tuber morphology. Suggestions for farmers to continue cultivating beneng taro. The government should counsel the surrounding community about beneng taro, especially farmers who can preserve local commodities and support conservation efforts.